Can Online Transparency Improve Accountability? The Case of Portuguese Private Social Solidarity Institutions - Ferreira, Augusta (2022)
The development of the non-profit sector (NPS) in Portugal has been gaining relevance in recent times, particularly in the form of institutions whose purpose is to broaden and increase the response to the needs of the most needy and socially vulnerable citizens. The financing of Portuguese non-profit sector entities is essentially made up of income from their activity, donations and public or governmental support. Therefore, these entities face increasing pressure from their funders, users and citizens in general for a greater dissemination of good practices regarding the social impact they have on the community; in particular, they are increasingly required to be transparent in their activities. The main objective of this study was to analyse the level of accountability and transparency of the private social solidarity institutions (IPSS) of the municipality of Porto. To this end, the websites of these institutions were analysed, using a qualitative and quantitative methodology, using the application of the transparency index Enhancement of an Accountability Guide for Learning E-Government. This analysis allowed us to verify that there are still a considerable number of entities that do not have an institutional website, and those that do, have a low level of transparency